Differences in Mean Anti-Pertussis Antibody Levels in Children with Acellular Pertussis Immunization and Whole Pertussis Without Booster - Rezki, Wenny Rahmalia; Rinang Mariko; Rizanda Machmud; Rusdi; Asrawati; Indra Ihsan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: The incidence of pertussis is increasing every year, especially in developing countries. Low immunization coverage and decreased immunity are some of the factors causing the re-increase in pertussis cases. The protection provided by the pertussis vaccine whole and acellular pertussis given as a baby will decrease with age. This study aims to determine the difference in mean levels of anti-pertussis antibodies in children who received acellular pertussis and whole pertussis immunization without a booster. Methods: A cross-sectional study was carried out at the pediatric polyclinic of Dr. M. Djamil General Hospital Padang from December 2022 to December 2023. Research subjects were children aged 5-9 years with a history of whole pertussis immunization (DPwT) 3 times or acellular pertussis immunization (DPaT) 3 times. The research subjects were examined for anti-pertussis antibody titers using the ELISA technique. Results: Thirty-four children with a history of DPwT immunization 3 times and 34 children with a history of DPwT immunization 3 times were research subjects, with mean age 6.94±1.49 in the DPwT group and 6.88 ±1.61 in the DPaT group. The mean anti-pertussis antibody level in the DPwT group (9.54 IU/mL) was higher than the DPaT group (6.96 IU/mL) but was not statistically significant (p>0.05). The average antibody results showed that the antibody levels in both groups were below the antibody titer threshold that provides protection against pertussis. The results of the analysis showed that there was a significant difference in the incidence of AEFI between the DPwT and DPaT immunization groups (p<0.05). Conclusion: There was no difference in anti-pertussis antibody levels in children who received DPwT and DPaT immunization 3 times. Pertussis immunization is a required booster so that antibody levels are sufficient to provide protection against pertussis.